Factors Influencing Rice Seed Production and Distribution: A Case Study of Ogan Komering Ilir Regency, South Sumatra. - Winnie Andhini; Muhammad Yazid; Riswani Riswani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Superior seed breeding is one of the food products that has the opportunity to be developed in an agribusiness system. The agribusiness system concerns all activities in the agricultural sector ranging from the upstream industry, farming, downstream industry to its distribution to consumers. This study aims to analyze factors related to seed production and distribution problems (government, breeders, markets, and users) in OKI Regency as one of the largest rice producing region in South Sumatera . The selection of the research location used the purposive sampling method, while the sample withdrawal used non-probability sampling by taking samples of breeder farmers in Bumi Agung Village, Lempuing District, OKI Regency. There are 60 rice seed breeders in this village who  were purposively selected as a sample of this study. Primary data in this study was collected by means of a survey using a questionnaire and analyzed using SEM and CLD. The results of the study showed that the factors that have a significant influence on seed production in seed breeding in OKI Regency are the end-user subsystem which includes seed availability, timeliness, and price at the consumer level and the input subsystem which includes seeds, fertilizer use, pesticide use, and agricultural tools and machinery with a positive influence direction. Meanwhile, the distribution of seeds from seed breeding in OKI Regency is an end-user subsystem which includes seed availability, timeliness, and prices at the consumer level, harvest subsistence and post-harvest which includes harvesting, drying, cleaning, sorting, and storage procedures and input subsystems which include seeds, fertilizer use, pesticide use, and agricultural tools and machinery.